Hybrid fuzzy PID controller design for ball and beam system / Nur Sakinah Abdul Aziz … [et al.] - Abdul Aziz, Nur Sakinah; Ishak, Norlela; Adnan, Ramli; Tajjudin, Mazidah (Universiti Teknologi MARA, 2019)
This research was focusing on the design of fuzzy logic PI+PD controller for ball and beam system. PID controller is mostly used in industrial applications. However, PID controller is not always an efficient combination for every type of system application. Due to some weaknesses that have been realized in conventional PID controller in term of error elimination and overshoot problems, fuzzy PI+PD was proposed for the system being considered. This paper presents the performance gained from Fuzzy PI+PD controller compared to Fuzzy PID. Based on simulations, the proposed controller had shown better performance compared to the full composite PID controller.